Comparative Efficacy of Silver Metallic Plastic Mulch, Botanicals and Insecticides in Controlling Tomato Yellow Leaf Curl Disease - Akter, S; Hossain, MB; Akter, S; Hasan, T; Mahmud, AU (SAARC Journal of Agriculture, 2021)
Tomato Yellow Leaf Curl caused by Tomato Yellow Leaf Curl Virus (TYLCV) is one of the most important diseases of tomato causing heavy losses in yield and quality of fruits. Damage caused through phloem feeding and transmission of TYLCV by the insect vectors whitefly (Bemisiatabaci). In this study the competence of silver metallic plastic mulch, botanicals and insecticides were assessed to manage the Tomato Yellow Leaf Curl Virus (TYLCV) by controlling the insect vectors. In total 7 treatments including control were considered viz. T1=Imidacloprid, T2= ACmix, T3= Subicron, T4= Neemax, T5= Multineem, T6 = Silver metallic plastic mulch and T7= Control. All the treatments showed significant influence on different assayed parameters in the test crop tomato. The lowest disease incidence, disease severity and whitefly association was found in T6 treatment (silver metallic plastic mulch) that was 2.87%, 1.72% and 2.0% at 60 days after transplanting (DAT) respectively. While the highest disease incidence, disease severity and whitefly association were found in T7 treatment (control treatment) that was 14.71%, 46.22% and 18, respectively, at 60 DAT. From the relationship study between disease incidence and disease severity with whitefly association, it was revealed that disease incidence and severity of TYLCV was increased with increasing of whitefly population and vice-versa. Among the treatments, growth parameters, yield and yield attributers were also found better in T6treatment (silver metallic plastic mulch). Silver metallic plastic mulch is the best option to manage the TYLCV by controlling the insect vectors, whitefly instead of insecticides. SAARC J. Agri., 18(2): 77-86 (2020)